Economic principles of commodity taxation - Christiansen, Vidar 1948-; Smith, Stephen 1955- (Cambridge University Press, 2021)
The authors provide a broad overview of economic aspects of commodity taxation, focussing in particular on theory and on policy applications in OECD countries. Some major papers in public economics have discussed whether these taxes should be levied at a uniform rate, or whether different commodities should be taxed differently, for reasons of either equity or efficiency. The authors begin with this question, and then discuss further issues, including the economic incidence of commodity taxes, the properties of the VAT, the taxation of financial services, the international aspects of commodity taxation, and environmental and health policy aspects
Keywords: OECD; Commercial products / Taxation; Taxation of articles of consumption; Fiscal policy; Verbrauchsteuer; Steuertheorie